Particularism vs unification: elaboration and adoption of the Grand Duchy of Lithuania Statute of 1588 - Padalinski, Uladzimir A. (Journal of the Belarusian State University. History, 2018)
The study is devoted to the problem of the coexistence of particularistic and unifying tendencies in the socio-political life of the XVI century’s Commonwealth. The example of the Grand Duchy of Lithuania Third Statute’s drafting shows the attempts of the Lithuanian (in the historical meaning) political nation to retain its own system of law. On the other hand, it shows the intention of the Polish nobility to unify the law of the two subjects of the Commonwealth. The author’s conception of the process of the Statute elaboration and adoption is given. New information is provided that permits reconsidering some of the traditional postulates fixed in the problem’s historiography. The study’s results are important for the comprehensive research of the political history of the Commonwealth, including its state, parliamentary and legal system, and relationsbetween the Grand Duchy of Lithuania and the Polish Kingdom.
Keywords: Статут ВКЛ; Вялікае Княства Літоўскае; Рэч Паспалітая; шляхта; партыкулярызм; уніфікацыя; павятовыя соймікі; вальны сойм